Implementasi Sholat Dhuha Berjama’ah dalam Pembentukan Karakter Siswa yang Berakhlakul Karimah - Sulistia, Nadia Eka; Setyawan, Agung; Widayati, Sih (maktab: Jurnal Pendidikan dan Teknologi, 2024)
This study aims to examine the implementation of congregational dhuha prayers in shaping the character of students who are morally good at SDN Tanjung Jati 2. Student character building is an important need amid the challenges of globalization and social changes that often override moral values. Observation, interviews, and documentation are used in a case study approach using a deskriptif qualitative methodology in this research. The outcomes demonstrated that the implementation of congregational dhuha prayers at SDN Tanjung Jati 2 not only brought students closer to Allah SWT but also helped shape the characters of discipline, responsibility, cooperation, and self-control. This dhuha prayer habit has proven effective in reducing negative behaviors such as delinquency and bullying, as well as improving student morale. Thus, congregational dhuha prayers at school play an important role in producing a generation that is morally good and has good spiritual intelligence.